Alterations in plasma antioxidants during reperfusion of the ischemic small intestine in rats - Papezíková, Ivana; Lojek, Antonín; Cízová, Hana; Cíz, Milan (Research in veterinary science, 2006)
The aim of this study was to evaluate the contribution of three plasma antioxidants (albumin, uric acid, SH groups) to the plasma total peroxyl radical-trapping antioxidant capacity (TRAP) in 2 and 4 h of intestinal reperfusion in rats. TRAP increased significantly both after 2 and 4 h of reperfusion. Neither albumin nor SH groups contributed significantly to this increase. TRAP was strongly influenced by the increase in uric acid concentration and also probably by the cell destruction caused by oxidative stress. Since the TRAP increase was accompanied by an increase in the level of thiobarbituric acid reactive substances (TBARS, a marker of lipid peroxidation), we can conclude that even such a large increase in TRAP is not sufficient to prevent the progression of lipid peroxidation and oxidative stress.
Keywords: Animals; Peroxides; kyselina močová; reperfuzní poškození; Antioxidants; Female; Rats, Wistar; oxidační stres; tenké střevo; ženské pohlaví; peroxidy; Intestine, Small; Oxidative Stress; sulfhydrylové sloučeniny; Reactive Oxygen Species; sérový albumin; peroxidace lipidů; Lipid Peroxidation; Reperfusion Injury; antioxidancia; Sulfhydryl Compounds; reaktivní formy kyslíku; krysa rodu Rattus; Serum Albumin; Ischemia; ischemie; zvířata; Uric Acid; Rats; potkani Wistar